2004
DOI: 10.1021/je049787p
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity and Viscosity of 1-Allyl-3-methyl-imidazolium Chloride + Water and + Ethanol from 293.15 K to 333.15 K

Abstract: The room-temperature ionic liquid 1-allyl-3-methyl-imidazolium chloride [amim][CI] was synthesized. The conductivities and viscosities of [amim][CI] + water and + ethanol binary mixtures were determined in the temperature range from 293.15 K to 333.15 K, and the mole fraction of the solvents in the mixtures was in the range of 0 to 0.80 for water and 0 to 0.55 for ethanol. The conductivities of the mixtures increased with increasing concentration of the solvents and temperature in the solvent concentration ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 21 publications
4
69
0
Order By: Relevance
“…It was reported having m.p. of ∼17 • C and viscosity of 685 mPa s at 30 • C (Zhang et al, 2005); but a different viscosity value (1127.7 mPa s at 30 • C) appeared in the Supporting Information of a recent paper (Remsing et al, 2008), while another group obtained much lower viscosities of 66 mPa s at 20 • C and 44.7 mPa s at 30 • C (Xu et al, 2005). However, a recent study suggested this IL crystallizes after purification (m.p.…”
Section: Methodsmentioning
confidence: 98%
“…It was reported having m.p. of ∼17 • C and viscosity of 685 mPa s at 30 • C (Zhang et al, 2005); but a different viscosity value (1127.7 mPa s at 30 • C) appeared in the Supporting Information of a recent paper (Remsing et al, 2008), while another group obtained much lower viscosities of 66 mPa s at 20 • C and 44.7 mPa s at 30 • C (Xu et al, 2005). However, a recent study suggested this IL crystallizes after purification (m.p.…”
Section: Methodsmentioning
confidence: 98%
“…In the same work, it was also concluded that the presence of water and other molecular co-solvents reduces the viscosity of ILs. For example, viscosities of binary mixtures [112] While the addition of molecular solvents to an IL decreases the solution viscosity, the addition of cellulose increases drastically the viscosity of the mixture. Concentrated cellulose/IL solutions show non-Newtonian behavior.…”
Section: Viscosity Of Concentrated Cellulose Solutions In Ilsmentioning
confidence: 99%
“…These papers mainly report these quantities for whole composition range of ionic liquids in water, and only some other works have been performed for dilute region solution of ionic liquids [7][8][9][10][11][12][13][14][15][16]. It is well known that ionic liquids can be viewed as kind of organic electrolyte.…”
Section: Introductionmentioning
confidence: 99%